A composite material for high-strength pipeline and preparation method thereof
By using long carbon chain semi-aromatic nylon and composite reinforced fillers to improve the mechanical properties of polyamide fibers, it solves its glass transition temperature and water absorption problems, achieves the satisfaction of high strength and toughness requirements, and expands its application scope.
Patent Information
- Application Number
- CN202411666471.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-11-21
AI Technical Summary
The existing polyamide fibers have low glass transition temperature, low melting point, low heat resistance and large water absorption, resulting in poor dimensional stability and insufficient mechanical strength of the product, which limits the further expansion of its application range.
Long carbon chain semi-aromatic nylon is used as the matrix resin, and glass fibers, carboxylated carbon nanotubes and nanosilica particles are added as composite reinforcement fillers. Combined with aminosilane coupling agent, improve the mechanical properties and toughness of the composite material and reduce water absorption. Rate.
It improves the mechanical strength and toughness of composite materials, solves the floating fiber problem of glass fiber reinforced materials, enhances the surface finish and bonding strength of the product, and broadens its application in fields with high requirements for high strength and toughness.
Smart Images

Figure OYIGGZGSH2MNNQNG4PNKSSUENBZW4ABZWQHWKQOB 
Figure REN1ZG4A3YLSNFJNN5Y01OFHPBZ7XJAVDR6B8X6L
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer composite materials, and particularly relates to a composite material for high-strength pipelines and a preparation method thereof. Background Art
[0002] Polyamide, commonly known as nylon, is a polymer with amide-based repeating structural units on the polymer chain. Polyamide can be obtained by ring-opening polymerization of lactam, or by polycondensation of dibasic acid and diamine. In recent years, special nylon varieties such as star-shaped nylon made from polyamine and diacid or polyacid and diamine have appeared. Polyamide plastic is developed on the basis of polyamide fiber. It is the earliest thermoplastic plastic that can withstand loads. Although the initial development and application field is fiber, due to the strong competition from synthetic fibers such as polyethylene terephthalate fiber (polyester, referred to as PET), the use of polyamide fiber has grown slowly. The use of polyamide as an engineering plastic was developed late, but due to its excellent comprehensive properties, such as excellent mechanical properties, good electrical properties, solvent resistance, wear resistance, self-lubrication, oil resistance, self-extinguishing, corrosion resistance and good processing performance, the application field of polyamide has been continuously expanded, and the production capacity and output of polyamide are increasing sharply every year. Polyamide resin has become the engineering plastic with the largest amount and the widest application field. The main application areas of polyamide engineering plastics are automobiles, machinery, electronics and electrical appliances, textiles and weapons, aerospace, etc. Since the 1990s, the output has maintained a rapid growth momentum.
[0003] Among the five major engineering plastics (polyamide, polycarbonate, polyoxymethylene, polyphenylene ether, polyester), polyamide resin has the largest output, the most varieties, and the widest application. The tonnage used in modified structural plastics is second only to ABS and polypropylene, ranking third. In recent years, in addition to the steady growth of major varieties such as PA6 and PA66, due to the development of industries such as automobiles and electronic appliances, the importance of PA11, PA12, PA46, PA1212 and some aromatic polyamides, semi-aromatic polyamides and some modified nylon products as special applications is also gradually increasing. In addition, the continuous optimization and innovation of new raw material production routes and production processes have given it broad application development prospects. In particular, the rapid development of cutting-edge technology industries marked by aerospace and high-capacity, high-precision electronic computers and communication equipment and related fields has promoted the development of special polyamide products such as aromatic polyamides and semi-aromatic polyamides with high heat resistance and high corrosion resistance, and their market demand has gradually increased.
[0004] The performance of nylon is closely related to its molecular structure. Among the nylon varieties that have been industrially produced and applied, aliphatic nylon is the main one, which has the advantages of fast crystallization speed, high crystallinity, certain heat resistance, good flexibility, fluidity and high mechanical strength, and is widely used in various fields. However, due to the low glass transition temperature, low melting point and low heat resistance of aliphatic nylon, and the high content of amide groups in the molecular structure, it has high water absorption, resulting in poor dimensional stability of the product, and low impact strength and poor mechanical strength in dry state or at low temperature, which limits the further expansion of its application range. Summary of the invention
[0005] In order to solve the above problems existing in the prior art, the present invention provides a composite material for high-strength pipes and a preparation method thereof. The present invention selects long carbon chain semi-aromatic nylon as the matrix resin to not only improve the mechanical strength of the composite material, but also improve its toughness, and has the characteristic of easy processing. At the same time, composite reinforcing fillers and other processing aids are added to improve the comprehensive performance of the composite material and broaden the application field.
[0006] The present invention adopts the following technical solution:
[0007] A composite material for high-strength pipes, comprising the following components in parts by weight:
[0008] 70-80 parts of long carbon chain semi-aromatic nylon, 15-20 parts of glass fiber, 3-10 parts of carboxylated carbon nanotubes, 1-6 parts of nano silicon dioxide particles, 2-4 parts of aminosilane coupling agent, 0-3 parts of lubricant, and 0-3 parts of antioxidant.
[0009] By reducing the content of amide groups in nylon and increasing the length of methylene groups, the water absorption rate can be effectively reduced. Long carbon chain nylon with a carbon number greater than 10 in the molecular structural unit effectively reduces the water absorption rate of the product, but the glass transition temperature and melting point are also lower than those of short chain nylon. Introducing aromatic rings in the main chain of aliphatic nylon molecules is conducive to improving the above shortcomings. The use of long carbon chain semi-aromatic nylon as a matrix resin material meets the application of composite materials in fields with high strength and toughness requirements such as pipelines. In order to further improve the mechanical properties of long carbon chain semi-aromatic nylon composite materials, the present invention adds glass fiber, carboxylated carbon nanotubes, and nano-silicon dioxide particles to reinforce the filler. Glass fiber is commonly used in fiber-reinforced polymer composite materials, especially when the addition amount is high, the tensile, bending, impact and other mechanical properties and heat deformation temperature of the composite material can be significantly improved. Glass fiber is widely used in the field of nylon material reinforcement due to its relatively low price and excellent comprehensive performance. However, when the amount of glass fiber is large, there is a problem of reduced processing performance and the floating fiber phenomenon is prone to occur. In order to overcome this problem, the present invention adds a certain amount of carboxylated carbon nanotubes and nano-silicon dioxide particles. The surface of the carboxylated carbon nanotubes has a large number of carboxyl active groups, which have excellent compatibility with glass fibers and polar polyamide resins. During the melt blending process, the linear carboxylated carbon nanotubes and granular nano-silicon dioxide particles can effectively promote the dispersion of glass fibers, prevent the composite material from floating fibers, and improve the surface finish of the product. Moreover, the linear carboxylated carbon nanotubes and glass fibers are interlaced to form a mesh structure, and the nano-silicon dioxide particles are dispersed therein, which effectively disperses the stress on the product, prevents stress concentration, and improves the mechanical properties of the composite material. Nano-silicon dioxide is selected as a granular reinforcing filler not only because of its low cost; more importantly, its surface hydrophilicity is more balanced than that of fillers such as calcium carbonate and titanium dioxide, which is conducive to the modification of the coupling agent and the dispersion in the resin, so as to achieve the purpose of synergistic modification with the carboxylated carbon nanotubes. The amino groups in the aminosilane coupling agent molecules can react with the carboxyl groups on the surface of carboxyl carbon nanotubes, and the other functional groups can react with the adsorbed water on the surface of inorganic substances to form a strong bond, so that an interface layer is formed between the glass fiber, carboxyl carbon nanotubes, nano-silica particles composite reinforcing filler and the resin matrix to transfer stress, thereby enhancing the bonding strength and improving the performance of the composite material. However, the amount of aminosilane coupling agent should not be too much, otherwise it will affect the processing performance of long carbon chain semi-aromatic nylon.
[0010] Furthermore, the composite material for high-strength pipes contains the following components by weight: 70-80 parts of long carbon chain semi-aromatic nylon, 15-20 parts of glass fiber, 4-7 parts of carboxylated carbon nanotubes, 2-4 parts of nano-silica particles, 2-4 parts of aminosilane coupling agent, 1 part of lubricant, and 1 part of antioxidant. The mechanical properties of the material are improved by adding glass fiber, carboxylated carbon nanotubes, and nano-silica particles to composite reinforcing fillers. In combination with an appropriate amount of aminosilane coupling agent, the compatibility of glass fiber, carboxylated carbon nanotubes, nano-silica particles and resin and the interaction between molecular chains can be improved, so that the reinforcing and toughening effects of the fillers can be fully exerted, and the rigidity and toughness of the final product are improved, and the problem of floating fibers on the surface of glass fiber reinforced materials is solved. When the amount of carboxylated carbon nanotubes or nano-silica particles is small, the effect of isolating and dispersing glass fibers is limited; when the amount is too much, the agglomeration of nanofillers may occur, which is not conducive to the improvement of the mechanical properties of the composite material.
[0011] Furthermore, the long carbon chain semi-aromatic nylon is at least one of PA9T, PA10T, PA11T, PA12T and PA14T.
[0012] Furthermore, the glass fiber is alkali-free glass fiber.
[0013] Furthermore, the carboxylated carbon nanotubes are obtained by oxidizing multi-walled carbon nanotubes using a mixed solution of concentrated sulfuric acid and concentrated nitric acid.
[0014] Furthermore, the specific preparation process of the carboxylated carbon nanotubes is: 5-10g of multi-walled carbon nanotubes are placed in a container with a stirring device, and then 60-80mL of a mixed solution of 98wt% concentrated sulfuric acid and 68wt% concentrated nitric acid are added, and heated and stirred for reaction; after the reaction is completed, the carboxylated carbon nanotubes are washed to neutrality and dried to obtain the carboxylated carbon nanotubes.
[0015] Furthermore, the volume ratio of concentrated sulfuric acid to concentrated nitric acid is 3:1; the reaction temperature is 55-65° C., and the reaction time is 3-5 h.
[0016] Furthermore, the aminosilane coupling agent is at least one of γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, and γ-aminopropylmethyldiethoxysilane.
[0017] Furthermore, the average particle size of the nano-silicon dioxide particles is 100-200 nm. The average particle size is the volume median particle size obtained by laser scattering measurement according to ISO13320.
[0018] Furthermore, the lubricant is at least one of pentaerythritol stearate, stearate, silicone powder, and talcum powder; and the antioxidant is a phosphite antioxidant or a hindered phenol antioxidant.
[0019] On the other hand, the present invention also provides a method for preparing a composite material for a high-strength pipeline, comprising the following steps:
[0020] (1) Drying the long carbon chain semi-aromatic nylon in a dryer;
[0021] (2) Weighing the dried long carbon chain semi-aromatic nylon, carboxylated carbon nanotubes, nano-silica particles, aminosilane coupling agent, lubricant, and antioxidant according to a ratio, and mixing them evenly to obtain a mixture;
[0022] (3) feeding the mixed material into the main feed port of a twin-screw extruder; adding glass fiber into the side feed port of the twin-screw extruder, and melt-extruded through the twin-screw extruder to obtain a composite material for a high-strength pipe; wherein the extrusion temperature is 300-330° C.; and the screw speed is 500-600 rpm.
[0023] Compared with the prior art, the beneficial effects of the present invention are as follows: the use of long carbon chain semi-aromatic nylon as the matrix resin material satisfies the application of composite materials in fields with high strength and toughness requirements such as pipelines. Linear carboxylated carbon nanotubes and granular nano-silica particles can effectively promote the dispersion of glass fibers and improve the surface finish of products. The aminosilane coupling agent forms an interface layer between the glass fibers, carboxylated carbon nanotubes, nano-silica particles composite reinforcing fillers and the resin matrix to transfer stress, thereby enhancing the bonding strength and improving the performance of the composite material. The mechanical properties of the material are improved by adding glass fibers, carboxylated carbon nanotubes, and nano-silica particles composite reinforcing fillers. In combination with an appropriate amount of aminosilane coupling agent, the compatibility of glass fibers, carboxylated carbon nanotubes, nano-silica particles and resins and the interaction between molecular chains can be improved, thereby giving full play to the reinforcing and toughening effects of the fillers and solving the problem of surface floating fibers of glass fibers. DETAILED DESCRIPTION
[0024] The present invention is further described in detail below in combination with specific implementation methods using examples so that the advantages of the present invention can be more easily understood by those skilled in the art, but it is not intended to limit the protection scope of the present invention.
[0025] Example 1
[0026] A composite material for high-strength pipes, comprising the following components in parts by weight:
[0027] 70 parts of long carbon chain semi-aromatic nylon PA12T, 15 parts of alkali-free glass fiber, 4 parts of carboxylated carbon nanotubes, 2 parts of nano-silica particles, 2 parts of aminosilane coupling agent, 1 part of lubricant, and 1 part of antioxidant 1098; the aminosilane coupling agent is γ-aminopropyltriethoxysilane; the average particle size of the nano-silica particles is 100 nm; and the lubricant is zinc stearate.
[0028] Example 2
[0029] A composite material for high-strength pipes, comprising the following components in parts by weight:
[0030] 80 parts of long carbon chain semi-aromatic nylon PA12T, 20 parts of alkali-free glass fiber, 7 parts of carboxylated carbon nanotubes, 4 parts of nano-silica particles, 4 parts of aminosilane coupling agent, 3 parts of lubricant, and 3 parts of antioxidant 1098; the aminosilane coupling agent is γ-aminopropyltrimethoxysilane; the average particle size of the nano-silica particles is 200nm; and the lubricant is silicone powder.
[0031] Example 3
[0032] A composite material for high-strength pipes, comprising the following components in parts by weight:
[0033] 70 parts of long carbon chain semi-aromatic nylon PA12T, 20 parts of alkali-free glass fiber, 4 parts of carboxylated carbon nanotubes, 4 parts of nano-silica particles, 2 parts of aminosilane coupling agent, 3 parts of lubricant, and 1 part of antioxidant 1098; the aminosilane coupling agent is γ-aminopropyltriethoxysilane; the average particle size of the nano-silica particles is 150nm; and the lubricant is talcum powder.
[0034] Example 4
[0035] A composite material for high-strength pipes, comprising the following components in parts by weight:
[0036] 72 parts of long carbon chain semi-aromatic nylon PA12T, 16 parts of alkali-free glass fiber, 5 parts of carboxylated carbon nanotubes, 3 parts of nano-silica particles, 2.5 parts of aminosilane coupling agent, 1 part of lubricant, and 1 part of antioxidant 1098; the aminosilane coupling agent is γ-aminopropyltriethoxysilane; the average particle size of the nano-silica particles is 150nm; and the lubricant is calcium stearate.
[0037] Example 5
[0038] A composite material for high-strength pipes, comprising the following components in parts by weight:
[0039] 78 parts of long carbon chain semi-aromatic nylon PA12T, 18 parts of alkali-free glass fiber, 6 parts of carboxylated carbon nanotubes, 3.5 parts of nano-silica particles, 3 parts of aminosilane coupling agent, 3 parts of lubricant, and 2 parts of antioxidant 1098; the aminosilane coupling agent is γ-aminopropyltrimethoxysilane; the average particle size of the nano-silica particles is 150nm; and the lubricant is talcum powder.
[0040] Example 6
[0041] A composite material for high-strength pipes, comprising the following components in parts by weight:
[0042] 76 parts of long carbon chain semi-aromatic nylon PA12T, 17 parts of alkali-free glass fiber, 5 parts of carboxylated carbon nanotubes, 3 parts of nano-silica particles, 3 parts of aminosilane coupling agent, 1 part of lubricant, and 2 parts of antioxidant 1098; the aminosilane coupling agent is γ-aminopropyltriethoxysilane; the average particle size of the nano-silica particles is 150nm; and the lubricant is talc.
[0043] Example 7
[0044] A composite material for high-strength pipes, comprising the following components in parts by weight:
[0045] 76 parts of long carbon chain semi-aromatic nylon PA12T, 17 parts of alkali-free glass fiber, 3 parts of carboxylated carbon nanotubes, 3 parts of nano-silica particles, 3 parts of aminosilane coupling agent, 1 part of lubricant, and 2 parts of antioxidant 1098; the aminosilane coupling agent is γ-aminopropyltriethoxysilane; the average particle size of the nano-silica particles is 150nm; and the lubricant is talcum powder.
[0046] Example 8
[0047] A composite material for high-strength pipes, comprising the following components in parts by weight:
[0048] 76 parts of long carbon chain semi-aromatic nylon PA12T, 17 parts of alkali-free glass fiber, 10 parts of carboxylated carbon nanotubes, 3 parts of nano-silica particles, 3 parts of aminosilane coupling agent, 1 part of lubricant, and 2 parts of antioxidant 1098; the aminosilane coupling agent is γ-aminopropyltriethoxysilane; the average particle size of the nano-silica particles is 150nm; and the lubricant is talc.
[0049] Example 9
[0050] A composite material for high-strength pipes, comprising the following components in parts by weight:
[0051] 76 parts of long carbon chain semi-aromatic nylon PA12T, 17 parts of alkali-free glass fiber, 5 parts of carboxylated carbon nanotubes, 1 part of nano-silica particles, 3 parts of aminosilane coupling agent, 1 part of lubricant, and 2 parts of antioxidant 1098; the aminosilane coupling agent is γ-aminopropyltriethoxysilane; the average particle size of the nano-silica particles is 150nm; and the lubricant is talcum powder.
[0052] Example 10
[0053] A composite material for high-strength pipes, comprising the following components in parts by weight:
[0054] 76 parts of long carbon chain semi-aromatic nylon PA12T, 17 parts of alkali-free glass fiber, 5 parts of carboxylated carbon nanotubes, 6 parts of nano-silica particles, 3 parts of aminosilane coupling agent, 1 part of lubricant, and 2 parts of antioxidant 1098; the aminosilane coupling agent is γ-aminopropyltriethoxysilane; the average particle size of the nano-silica particles is 150nm; and the lubricant is talc.
[0055] Comparative Example 1
[0056] A composite material for high-strength pipes, comprising the following components in parts by weight:
[0057] 76 parts of long carbon chain semi-aromatic nylon PA12T, 17 parts of alkali-free glass fiber, 0 parts of carboxylated carbon nanotubes, 8 parts of nano-silica particles, 3 parts of aminosilane coupling agent, 1 part of lubricant, and 2 parts of antioxidant 1098; the aminosilane coupling agent is γ-aminopropyltriethoxysilane; the average particle size of the nano-silica particles is 150nm; and the lubricant is talcum powder.
[0058] Comparative Example 2
[0059] A composite material for high-strength pipes, comprising the following components in parts by weight:
[0060] 76 parts of long carbon chain semi-aromatic nylon PA12T, 17 parts of alkali-free glass fiber, 8 parts of carboxylated carbon nanotubes, 0 parts of nano-silica particles, 3 parts of aminosilane coupling agent, 1 part of lubricant, and 2 parts of antioxidant 1098; the aminosilane coupling agent is γ-aminopropyltriethoxysilane; the average particle size of the nano-silica particles is 150nm; and the lubricant is talcum powder.
[0061] Comparative Example 3
[0062] A composite material for high-strength pipes, comprising the following components in parts by weight:
[0063] 76 parts of long carbon chain semi-aromatic nylon PA12T, 17 parts of alkali-free glass fiber, 5 parts of carboxylated carbon nanotubes, 3 parts of nano-silica particles, 1 part of aminosilane coupling agent, 1 part of lubricant, and 2 parts of antioxidant 1098; the aminosilane coupling agent is γ-aminopropyltriethoxysilane; the average particle size of the nano-silica particles is 150nm; and the lubricant is talc.
[0064] Comparative Example 4
[0065] A composite material for high-strength pipes, comprising the following components in parts by weight:
[0066] 76 parts of long carbon chain semi-aromatic nylon PA12T, 17 parts of alkali-free glass fiber, 5 parts of carboxylated carbon nanotubes, 3 parts of nano-silica particles, 6 parts of aminosilane coupling agent, 1 part of lubricant, and 2 parts of antioxidant 1098; the aminosilane coupling agent is γ-aminopropyltriethoxysilane; the average particle size of the nano-silica particles is 150nm; and the lubricant is talcum powder.
[0067] In the above embodiments and comparative examples,
[0068] The specific preparation process of carboxylated carbon nanotubes is as follows: 7g of multi-walled carbon nanotubes are placed in a container with a stirring device, and then 70mL of a mixed solution of 98wt% concentrated sulfuric acid and 68wt% concentrated nitric acid is added, and heated and stirred for reaction; after the reaction is completed, the mixture is washed to neutrality and dried to obtain the carboxylated carbon nanotubes; wherein the volume ratio of concentrated sulfuric acid to concentrated nitric acid is 3:1; the reaction temperature is 60°C, and the reaction time is 4h.
[0069] A method for preparing a composite material for a high-strength pipeline comprises the following steps:
[0070] (1) Drying the long carbon chain semi-aromatic nylon in a dryer;
[0071] (2) Weighing the dried long carbon chain semi-aromatic nylon, carboxylated carbon nanotubes, nano-silica particles, aminosilane coupling agent, lubricant, and antioxidant according to a ratio, and mixing them evenly to obtain a mixture;
[0072] (3) feeding the mixed material into the main feed port of a twin-screw extruder; adding glass fiber into the side feed port of the twin-screw extruder, and melt-extruded through the twin-screw extruder to obtain a composite material for a high-strength pipe; wherein the extrusion temperature is 316° C. and the screw speed is 550 rpm.
[0073] Performance test: The high-strength composite materials for pipes obtained in the examples and comparative examples were prepared into standard samples, and the tensile strength of the samples was tested according to ISO 527-2 standard; the bending strength of the samples was tested according to ISO 178 standard; and the notched impact strength of the samples was tested according to ISO 179 standard. The surface condition of the samples was observed and the surface smoothness was evaluated as A, B, C, and D; the level from A to D indicates that the floating fiber situation is getting more and more serious. The test results are shown in Table 1 below.
[0074]
[0075]
[0076] As can be seen from Table 1, the present invention uses long carbon chain semi-aromatic nylon as the matrix resin material to meet the application of composite materials in fields with high strength and toughness requirements such as pipelines. Linear carboxylated carbon nanotubes and granular nano-silica particles can effectively promote the dispersion of glass fibers and improve the surface finish of products. By adding glass fibers, carboxylated carbon nanotubes, and nano-silica particles to composite reinforcing fillers to improve the mechanical properties of the material, combined with an appropriate amount of aminosilane coupling agent, the compatibility of glass fibers, carboxylated carbon nanotubes, nano-silica particles and resins and the interaction between molecular chains can be improved, thereby giving full play to the reinforcing and toughening effects of fillers, and solving the problem of floating fibers on the surface of glass fibers. Further, it can be seen from Examples 6-10 that when the composite material for high-strength pipelines contains the following components in parts by weight: 70-80 parts of long carbon chain semi-aromatic nylon, 15-20 parts of glass fibers, 4-7 parts of carboxylated carbon nanotubes, 2-4 nano-silica particles, and 2-4 parts of aminosilane coupling agents, the reinforcing and toughening effects can be fully exerted between the fillers, and the surface of the product is smoother. Comparative Examples 1-2 show that during the melt blending process, the linear carboxylated carbon nanotubes and the granular nano-silica particles cooperate with each other to effectively promote the dispersion of glass fibers, prevent the composite material from floating fibers, and improve the surface finish of the product. Comparative Examples 3-4 show that the amino groups in the aminosilane coupling agent molecules can react with the carboxyl groups on the surface of the carboxylated carbon nanotubes to form an interface layer between the glass fibers, carboxylated carbon nanotubes, nano-silica particles, composite reinforcing fillers, and the resin matrix, transferring stress, thereby enhancing the bonding strength and improving the performance of the composite material; however, the amount of aminosilane coupling agent should not be too much, otherwise it is not conducive to the melt processing of long carbon chain semi-aromatic nylon and affects the improvement of product performance.
[0077] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A composite material for high-strength pipes, characterized in that: Contains the following components in parts by weight: 70-80 parts of long carbon chain semi-aromatic nylon, 15-20 parts of glass fiber, 3-10 parts of carboxylated carbon nanotubes, 1-6 parts of nano-silica particles, 2-4 parts of aminosilane coupling agent, 0-3 parts of lubricant, and 0-3 parts of antioxidant; The long carbon chain semi-aromatic nylon is at least one of PA9T, PA10T, PA11T, PA12T and PA14T; The average particle size of the nano silicon dioxide particles is 100-200 nm.
2. A composite material for high-strength pipes according to claim 1, characterized in that: The glass fiber is alkali-free glass fiber.
3. The composite material for high-strength pipes according to claim 1, characterized in that: The carboxylated carbon nanotubes are obtained by oxidizing multi-walled carbon nanotubes using a mixed solution of concentrated sulfuric acid and concentrated nitric acid.
4. A composite material for high-strength pipes as claimed in claim 3, characterized in that: The specific preparation process of the carboxylated carbon nanotubes is as follows: 5-10g of multi-walled carbon nanotubes are placed in a container with a stirring device, and then 60-80mL of a mixed solution of 98wt% concentrated sulfuric acid and 68wt% concentrated nitric acid are added, and heated and stirred for reaction; after the reaction is completed, the carbon nanotubes are washed to neutrality and dried to obtain the carboxylated carbon nanotubes.
5. The composite material for high-strength pipes according to claim 4, characterized in that: The volume ratio of the concentrated sulfuric acid to the concentrated nitric acid is 3:1; the reaction temperature is 55-65° C., and the reaction time is 3-5 hours.
6. The composite material for high-strength pipes according to claim 1, characterized in that: The aminosilane coupling agent is at least one of γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane and γ-aminopropylmethyldiethoxysilane.
7. The composite material for high-strength pipes according to claim 1, characterized in that: The lubricant is at least one of pentaerythritol stearate, stearate, silicone powder and talcum powder; the antioxidant is a phosphite antioxidant or a hindered phenol antioxidant.
8. The method for preparing the composite material for high-strength pipes according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) Drying the long carbon chain semi-aromatic nylon in a dryer; (2) Weighing the dried long carbon chain semi-aromatic nylon, carboxylated carbon nanotubes, nano-silica particles, aminosilane coupling agent, lubricant, and antioxidant according to a ratio, and mixing them evenly to obtain a mixture; (3) feeding the mixed material into the main feed port of a twin-screw extruder; adding glass fiber into the side feed port of the twin-screw extruder, and melt-extruded through the twin-screw extruder to obtain a composite material for a high-strength pipe; wherein the extrusion temperature is 300-330° C.; and the screw speed is 500-600 rpm.
Citation Information
Patent Citations
High temperature resistant enhanced thermoplastic composite material and preparation method thereof
CN107459816A
Nylon 6T composite material and preparation method thereof
CN111849159A